First data of Temnocephalidea (Temnocephala, Temnocephalidae, Turbellaria) in Vietnam - Bai, Thai Tran (Academia Journal of Biology, 2015)
First data of Temnocephalidea (Temnocephala, Temnocephalidae, Turbellaria) in Vietnam